An experimental investigation of the pressure on valve assembly of the comopressor - Tay, Javier. (2012)
There are many components in a reciprocating compressor that can be studied in detailed to improve the overall performance of the compressor. Many studies have been done to understand the different aspect of the components in order to improve. For example, the valve assembly of the compressor is one aspect that many engineers are trying to understand and further improve on such a complicated yet interesting component. The objective of this study is to optimize the design of the suction reed plate of a hermetic reciprocating compressor used in household appliances. The cooling capacity and COP (Coefficient of Performance) data’s are gathered using a calorimeter for suction reed plate with different shapes and stiffness values. The prototypes are prepared and designed using FEM (Finite Elements) and performance tests are carried out on a SJJ51C compressor.